EfficientNet B0 Algorithm for SIBI to Text and Audio Translation System - Zaizafuny, A Muflih; Wijayanti, Rieke Adriati; Dali, Sri Wahyuni (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The Indonesian Sign Language System (SIBI) serves as the fundamental mode of communication for the deaf and mute community in Indonesia. However, a significant communication gap exists as the general public often struggles to comprehend these signs. Leveraging advancements in Artificial Intelligence (AI), specifically Machine Learning, offers a solution to bridge this gap and improve accessibility. This research focuses on developing a SIBI sign language translation system that converts gestures into both text and audio formats, utilizing a Convolutional Neural Network (CNN) based on the EfficientNet B0 architecture. The model underwent rigorous training with varying epoch counts, ultimately identifying 35 epochs as the optimal duration to maximize performance while mitigating overfitting and underfitting risks. Experimental results from distance testing revealed an inverse relationship between accuracy and camera-to-hand distance: 74% at 5 cm, 64% at 25 cm, 52% at 45 cm, 41% at 55 cm, 28% at 65 cm, 26% at 75 cm, 16% at 85 cm, and 0% at 95 cm. These findings underscore distance as a critical factor. Overall, the application achieved an average accuracy of 76%, demonstrating its potential to facilitate effective communication and promote social inclusivity.